The Epidemiological Tuberculosis Situation in the Russian Penitentiary System: Main Trends and Challenges - V. V. Testov; V. S. Burykhin; M. E. Vostroknutov; S. A. Sterlikov (Туберкулез и болезни лёгких)
The article describes the current tuberculosis epidemiological situation in institutions of the penitentiary system including the combination of tuberculosis and HIV infection. The epidemic consequences of increased coverage of people living with HIV infection (PLHIV) with antiretroviral therapy (ART) were analyzed. By 2020, tuberculosis incidence dropped to 621 per 100,000. Tuberculosis mortality dropped to 6.8 per 100,000. The incidence of tuberculosis among PLHIV decreased from 3,490.6 per 100,000 population in 2014 to 2,014.2 per 100,000 population in 2020, while coverage of PLHIV with ART increased from 21.7 to 89.6%. The proportion of TB patients among PLHIV decreased from 10.4% in 2014 to 7.2% in 2020. The proportion of PLHIV among newly diagnosed TB patients remained high (34.4% in 2020). The prevalence of multiple drug resistant tuberculosis decreased to 557.6 per 100,000. Thus, in 2020, the epidemiological tuberculosis situation in the Russian penitentiary institutions continued to improve. The strategy to increase coverage of PLHIV with ART proved to be effective for prevention of tuberculosis in penitentiary settings. Multiple drug resistant tuberculosis presents a serious problem which forms the grounds for introduction of modern treatment protocols with innovative drugs to the Russian penitentiary institutions.